A Rare Cause of Lobular Panniculitis: Munchausen's Syndrome - Ajili Faida; Smiti Khanfir Monia; Hamzaoui Amira; Ben Ghorbel Imed; Lamloum Mounir; Houman Mohamed Habib (Case Reports in Medicine)
We describe a case of a 40-year-old woman who presented with ecchymoses of the right leg and who was found to have lobular panniculitis in biopsy due to Munchausen's Syndrome.